3(3-2х)+27=2(3+2х) 3х+2,7=9(х-1,1) 0,2(5х-2)=0,3(2х-1)-0,9 ! 15 !

зимлен зимлен    2   14.08.2019 06:50    0

Ответы
lehfff lehfff  04.10.2020 18:04
1) 9 - 6x +27 = 6 + 4x
     - 6x - 4 x = 6 - 9 - 27
     - 10x = - 30
        x = 3
2) 3x + 2,7 = 9x - 9,9
     3x - 9x = - 9,9 - 2, 7
      - 6x = 7, 2
       x = -  1, 2
3) x - 0, 4 = 0,6x - 0, 3 - 0,9
     x - 0,6x = - 0,3 - 0,9 + 0,4
      -0,4x = - 0, 8
        x = 2
ПОКАЗАТЬ ОТВЕТЫ
147387492 147387492  04.10.2020 18:04
1. 3(3-2х)+27=2(3+2х) 
9-6х+27=6+4х
4х+6х=9-6+27
10х=30
х=3

2. 3х+2.7=9(х-1.1)
3х-2.7=9х-9.9
9х-3х=9.9-2.7
6х=7.2
х=1.2

3. 0.2(5х-2)=0.3(2х-1)-0.9
х-0.4=0.6х-0.3-0.9
х-0.6х=0.4-0.3-0.9
0.4х=-0.8
х=-2
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра